Clinical significance of assessing ADAMTS-13 and von Willebrand factor level in COVID-19 convalescent pregnant women - N. R. Gashimova; K. N. Grigoreva; V. O. Bitsadze; L. L. Pankratyeva; J. Kh. Khizroeva; M. V. Tretyakova; Ya. M. Shammut; E. Iu. Iupatov; V. I. Tsibizova; J.-K. Gris; D. V. Blinov; A. D. Makatsariya (Акушерство, гинекология и репродукция, 2023)
Introduction. Coronavirus infection is associated with severe endotheliopathy, thromboinflammation and immunothrombosis leading to excessive release of von Willebrand factor (vWF) multimers from Weibel–Palade bodies, which can affect activity of ADAMTS-13 metalloproteinase (a disintegrin and metalloproteinase with thrombospondin type 1 motif, member 13) and the ADAMTS-13/vWF axis previously shown by us to be altered in non-pregnant women with severe COVID-19.  Aim: to study a clinical role of hemostasis activation particularly ADAMTS-13/vWF axis in pregnant women after COVID-19.  Materials and Methods. A prospective case–control study was conducted with pregnant women (n = 135) divided into 3 groups: group 1 included 45 women with prior COVID-19 during pregnancy, group 2 – 45 women in the acute phase of the infection during pregnancy, group 3 – 45 healthy pregnant women. The level of vWF and ADAMTS-13 was assessed in all patients.  Results. The concentration of vWF antigen (vWF:Ag) in the acute period of the disease in pregnant women with COVID-19 was significantly higher compared to the control group (p < 0.001). ADAMTS-13 level in pregnant women after COVID-19 did not differ from that of in control group, while vWF level was significantly higher in 66.7 % (30/45). The ADAMTS-13/vWF ratio was increased and significantly differed both in pregnant patients during the acute period of the disease (p < 0.001) and pregnant women after infection (p = 0.0002) compared with the control group.  Conclusion. Our results show that endotheliopathy was prominently manifested in pregnant women with COVID-19 and persisted for several months after disease. The ADAMTS-13/vWF ratio determines the pathway functioning, the risk of microcirculation disorders and clinical complications.